"CLUPS": A New Culture Medium for the Axenic Growth of Entamoeba histolytica. (11th July 2018) - Gonzalez-Salazar, F.; Meester, I.; Guzmán De La Garza, F. J.; De La Garza-Salinas, L. H.; Sampayo-Reyes, A.; Garza-Gonzalez, J. N.; Monsivais-Diaz, O.; Barba-Dávila, B. A.; Hernández-García, M. E.; Vargas-Villarreal, J.
Abstract : Amebiasis remains a major health problem in Mexico. Therefore, the search for better culture media and low-cost diagnostic and therapeutic tools is fundamental. We present a new culture medium for Entamoeba histolytica which allows the microbe to preserve its virulence factors and ability to induce hepatic abscesses in animal models. The novel CLUPS medium is an improved version of the PEHPS medium, previously designed in our laboratory. The main difference is the substitution of raw beef liver in PEHPS by raw beef lung in the CLUPS medium. To compare the performance of three-culture media (traditional TYI-S-33, PEHPS, and CLUPS), E. histolytica trophozoites were cultured in quintuplicate, followed by the evaluation of phospholipase activity and the induction of liver abscesses in golden hamsters. E. histolytica trophozoites grew significantly better in CLUPS medium than in TYI-S-33. Likewise, CLUPS-cultured trophozoites produced significantly more phospholipases than TYI-S-33-cultured trophozoites. Finally, trophozoites grown in any of the three tested media had similar potential to induce liver abscesses.